HIV Envelope Trimer Specific Immune Response Is Influenced by Different Adjuvant Formulations and Heterologous Prime-Boost - Apostólico, Juliana de Souza (PLoS One, 2016)
The development of a preventive vaccine against human immunodeficiency virus (HIV-1) infection is the most efficient method to control the epidemic. The ultimate goal is to develop a vaccine able to induce specific neutralizing, non-neutralizing antibodies and cellular mediated immunity (CMI). Humoral and CMI responses can be directed to glycoproteins that are normally presented as a trimeric spike on the virus surface (gp140). Despite safer, subunit vaccines are normally less immunogenic/effective and need to be delivered together with an adjuvant. The choice of a suitable adjuvant can induce effective humoral and CMI that utterly lead to full protection against disease. In this report, we established a hierarchy of adjuvant potency on humoral and CMI when admixed with the recombinant HIV gp140 trimer. We show that vaccination with gp140 in the presence of different adjuvants can induce high-affinity antibodies, follicular helper T cells and germinal center B cells. The data show that poly (I:C) is the most potent adjuvant to induce specific CMI responses evidenced by IFN-γ production and CD4(+)/CD8(+) T cell proliferation. Furthermore, we demonstrate that combining some adjuvants like MPL plus Alum and MPL plus MDP exert additive effects that impact on the magnitude and quality of humoral responses while mixing MDP with poly (I:C) or with R848 had no impact on total IgG titers but highly impact IgG subclass. In addition, heterologous DNA prime- protein boost yielded higher IgG titers when compare to DNA alone and improved the quality of humoral response when compare to protein immunization as evidenced by IgG1/IgG2a ratio. The results presented in this paper highlight the importance of selecting the correct adjuvant-antigen combination to potentiate desired cells for optimal stimulation.